Production of edible coating based on fruit and vegetable residues: application on minimally processed carrot (Daucus carota L.) (Scientia Agropecuaria, 2015)
The application of edible coatings obtainable from alternative biodegradable materials has gained attention as a promising treatment to prolong the shelf-life of fresh-cut vegetables. Thus, this work aimed to develop a biodegradable coating based on fruit and vegetable residues flour. Immersion coating strategy was studied on the quality of minimally fresh-cut carrots during refrigeration storage by means of weight loss, color variation, pH, titratable acidity and soluble solids content. Better performance was obtained for coated carrots, which exhibited a tendency to have lower whiteness index than uncoated counterparts and enhanced overall quality. Despite a drop in color saturation expressed by chroma values (varying from 59 to 46) was observed, color index presented a positive value for all samples (varying from 13 to 15) indicating orange color preservation throughout storage. Although color parameter was influenced by coating treatment, minor modifications occur over storage concerning weight loss, pH, titratable acidity and soluble content. Results obtained demonstrated the potential of the fruit and vegetable residues flour for edible coatings formulation. Practical application on minimally processed carrots supported its suitability to be used as an alternative coating material and constitute a motivating route to evaluate and optimize this alternative preservation technique.
Keywords: food preservation; minimal-processing; edible coating; agroindustrial residue